The Grand Ethiopian Renaissance Dam and the Nile Basin : implications for transboundary water cooperation - Yihdego, Zeray; Rieu-Clarke, Alistair; e (London : Taylor and Francis, 2017)
"The Grand Ethiopian Renaissance Dam (GERD) will not only be Africa's largest dam, but it is also essential for future cooperation and development in the Nile River Basin and East African region. This book, after setting out basin-level legal and policy successes and failures of managing and sharing Nile waters, articulates the opportunities and challenges surrounding the GERD through multiple disciplinary lenses. It sets out its possibilities as a basis for a new era of cooperation, its regional and global implications, the benefits of cooperation and coordination in dam filling, and the need for participatory and transparent decision making. By applying law, political science and hydrology to sharing water resources in general and to large-scale dam building, filling and operating in particular, it offers concrete qualitative and quantitative options that are essential to promote cooperation and coordination in utilising and preserving Nile waters. The book incorporates the economic dimension and draws on recent developments including: the signing of a legally binding contract by Egypt, Ethiopia and Sudan to carry out an impact assessment study; the possibility that the GERD might be partially operational very soon, the completion of transmission lines from GERD to Addis Ababa; and the announcement of Sudan to commence construction of transmission lines from GERD to its main cities. The implications of these are assessed and lessons learned for transboundary water cooperation and conflict management."--Provided by publisher
5 Changing cooperation dynamics in the Nile Basin and the role of the GERD6 GERD and hydropolitics in the Eastern Nile: from water-sharing to benefit-sharing? -- 7 Analysing the economy-wide impacts on Egypt of alternative GERD filling policies -- 8 Economic impact assessment of the Grand Ethiopian Renaissance Dam under different climate and hydrological conditions -- 9 From projecting hydroclimate variability to filling the GERD: upstream hydropower generation and downstream releases -- 10 Managing risks while filling the Grand Ethiopian Renaissance Dam
Print version record.
Keywords: Dams -- Ethiopia; Barrages; TECHNOLOGY & ENGINEERING -- Hydraulics; Dams; Ethiopia